Mejoramiento genético. Despliegue de caracteres - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The flow of germplasm from CIAT to national programs is described for the following regions: Central America and the Caribbean, Mexican highlands, Argentina, West Asia, and the Andean region (Colombia, Ecuador, and Peru). This flow is channeled through adaptation nurseries (VA), each country receiving the VA that corresponds to local grain color preferences: black, mottled, or yellow/beige. Each VA of a given color class is a uniform nursery, thus facilitating compilation of data and observations over sites. Tables showing the distribution of VA by color and country, and yield vs. environment correlations are included. (CIAT)